To the problem of selection of the conjunction and unconjunction constructions (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Material of the article is contained by the generalized exposition of the scientific approach to a selection, determination and character of types of compound sentences.
Keywords: compound sentence; conjunction sentence; unconjunction sentence